GPER mediates the angiocrine actions induced by IGF1 through the HIF-1α/VEGF pathway in the breast tumor microenvironment - De Francesco, Ernestina M.; Sims, Andrew H.; Maggiolini, Marcello; Sotgia, Federica; Lisanti, Michael P.; Clarke, Robert B. (Breast cancer research : BCR, 2017)
Background The G protein estrogen receptor GPER/GPR30 mediates estrogen action in breast cancer cells as well as in breast cancer-associated fibroblasts (CAFs), which are key components of microenvironment driving tumor progression. GPER is a transcriptional target of hypoxia inducible factor 1 alpha (HIF-1α) and activates VEGF expression and angiogenesis in hypoxic breast tumor microenvironment. Furthermore, IGF1/IGF1R signaling, which has angiogenic effects, has been shown to activate GPER in breast cancer cells. Methods We analyzed gene expression data from published studies representing almost 5000 breast cancer patients to investigate whether GPER and IGF1 signaling establish an angiocrine gene signature in breast cancer patients. Next, we used GPER-positive but estrogen receptor (ER)-negative primary CAF cells derived from patient breast tumours and SKBR3 breast cancer cells to investigate the role of GPER in the regulation of VEGF expression and angiogenesis triggered by IGF1. We performed gene expression and promoter studies, western blotting and immunofluorescence analysis, gene silencing strategies and endothelial tube formation assays to evaluate the involvement of the HIF-1α/GPER/VEGF signaling in the biological responses to IGF1. Results We first determined that GPER is co-expressed with IGF1R and with the vessel marker CD34 in human breast tumors ( n = 4972). Next, we determined that IGF1/IGF1R signaling engages the ERK1/2 and AKT transduction pathways to induce the expression of HIF-1α and its targets GPER and VEGF. We found that a functional cooperation between HIF-1α and GPER is essential for the transcriptional activation of VEGF induced by IGF1. Finally, using conditioned medium from CAFs and SKBR3 cells stimulated with IGF1, we established that HIF-1α and GPER are both required for VEGF-induced human vascular endothelial cell tube formation. Conclusions These findings shed new light on the essential role played by GPER in IGF1/IGF1R signaling that induces breast tumor angiogenesis. Targeting the multifaceted interactions between cancer cells and tumor microenvironment involving both GPCRs and growth factor receptors has potential in future combination anticancer therapies.